Examining the Impact of Cognitive and Emotional Factors on Consumer Behavioral Responses in Online Behavioral Advertising - Hossein Norouzi; Bahareh Osanlou; Ali Saleh Gohari (‫مدیریت بازرگانی)
Objective With the rapid advancement of technology, it has become possible to track consumers' behavior on the Internet. Consequently, marketers can tailor advertisements to align with consumers' needs and characteristics. However, this raises concerns about consumer privacy. Some researchers have concentrated on the positive aspects of Online Behavioral Advertising (OBA), while others have delved into its negative implications. Therefore, this study seeks to examine the impact of cognitive and affective factors on consumers' behavioral responses to OBA. It aims to explore both the positive and negative facets of this advertising approach.